Environmental education gaps: Women's mythical beliefs and perceptions of flood disasters - Aman, Abu (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Nationally, flood disasters have increased, which have a negative impact on all sectors of social life, especially on the daily lives of women. Methods: The research method uses a qualitative method by conducting interviews with women who live on Wonocolo Street, Jemur Wonosari Village, Wonocolo District, Surabaya, East Java from Neighborhood Flats/Rukun Tetangga (RT) and Residential Flats/Rukun Warga (RW) in the affected areas and conducting field observations and supporting literature reviews. Findings: Every year, during the rainy season, floods occur, which become an important problem in various countries. Because, many negative impacts are experienced by the community, both individually, groups and on the government system. This study aims to describe women's perceptions of flooding on Wonocolo Street, Jemur Wonosari Village, Wonocolo District, Surabaya, East Java, Indonesia about the occurrence, causes, and impacts of flooding on women as flood victims and on public awareness of the environment. Conclusion: The results of the study stated that the causes of flooding were high rainfall, houses being built too close together, careless waste disposal, lack of greenery, poor drainage and culvert construction, limited road access, limited culvert and drainage construction, limited wetlands, houses being built along rivers, and river silting. The impact of flooding is material losses in terms of buildings, income, and daily life. Novelty/Originality of this article: This study concluded that women on Wonocolo Street, Jemur Wonosari Village, Wonocolo District, Surabaya, East Java still believe in the prevailing myths and lack awareness of the importance of protecting the environment together.